The Influence of Technical Competencies and Psychological Well-being on the Competitiveness of Micro, Small, And Medium Enterprises - Prayudi, Ahmad; Pratiwi, Henny; Aulia, Muhammad Reza; Sari, Warsani Purnama (Bulletin of Counseling and Psychotherapy, 2023)
This study aims to assess the impact of participatory training on enhancing the psychological well-being and technical skills of Micro, Small, And Medium Enterprise (MSME) artisans in Tangkahan’s ecotourism sector. Fifty MSME participants, who had previously attended training sessions organized by government agencies and universities, were selected as respondents. The study employed observation and statistical analysis, specifically paired samples t-tests, to evaluate changes in knowledge and skills before and after the training. The results revealed a significant improvement in both the well-being and performance of participants, with t-values exceeding the t-table and significance values (p) below 0.05. Additionally, Structural Equation Modeling with Partial Least Squares (SEM-PLS) was utilized to analyze the interrelationships between variables and test the hypotheses. This approach provided a robust framework for evaluating the direct and indirect effects among the factors, enhancing the validity and depth of the findings. These findings highlight that participatory training improves the psychological well-being and technical skills of handicraft MSME actors in managing their businesses. This study also reveals that psychological well-being has a significant direct impact on technical skills and competitiveness. Additionally, technical skills directly influence competitiveness, while psychological well-being indirectly affects competitiveness through the mediation of technical skills. This study advocates for a holistic training approach that not only focuses on technical skill enhancement but also prioritizes psychological well-being to enhancing competitiveness. The success of MSMEs depend not only on technical skills but also on the psychological well-being such as job satisfaction, stress management, mental health, motivation and positive emotion of the workforce. By adopting this comprehensive strategy, future training programs can drive long-term improvements in both individual well-being and business performance, ensuring the resilience and competitiveness of MSMEs in Tangkahan’s ecotourism sector.